Relationship between substance misuse and depression among adolescents - Ermağan Çağlar, Eda; Türk, Tuğba (Journal of Dependence, 2018)
Objective: The aim of this research was to examine the relationship between substance use experience and depression symptoms in second grade high school students. Method: The questionnaire used in the research was developed by the researchers and the reliability value was analyzed. 350 students attending the second-grade high school participated in the survey by responding to the online questionnaire. Results: The most common depressive symptoms among students are believing they must be perfect (61.4%); being nervous and angry (55.4%); feeling loneliness (59.7%); frequent crying (48.8%) and skepticism (46.8%). It is found that the adolescents who have experienced the substance are tend to commit suicide 5 times; hurt themselves deliberately or try to kill themselves 4.74 times; feel so guilty 2.70 times; feel unhappy, sad, depressed and low-spirited 2.16 times; the thought of being hurt or misbehaved by others 2.14 times more than the adolescents who have not experienced it. Conclusion: In the research, the relationship between depression and substance dependence was shown and it was observed which substances constitute more risk for adolescents with depressive symptoms.